A Record of Holocene Climate Change from the Sunda Shelf, South China Sea - Woodson, Anna Lee (East Carolina University, 2014)
Variations in the East Asian Monsoon (EAM) control weather and regional climate conditions in the heavily populated, agriculturally dependent regions of eastern and southeast Asia. The South China Sea (SCS), especially the deep, northern SCS, has yielded many high-resolution Quaternary records of the EAM due to its high sedimentation rates and central location within the EAM system. The Sunda Shelf, a low-gradient, shallow region in the southwestern semi-enclosed SCS, is characterized by thin (~1 m) Holocene deposits and thus has not been a target for paleoclimate reconstructions. However, flooded fluvial paleochannels on the Sunda Shelf contain thicker, muddy Holocene sediments. Herein we test the hypothesis that the sediment fill of fluvial paleochannels contains a record of Holocene paleoclimate. Two piston cores were collected in fluvial paleochannels ~80 km offshore of Bintulu, Sarawak, Malaysia. Core D45, collected on the edge of a v-shaped paleochannel, exhibits ~7200 years of sediment accumulation, whereas core D42, retrieved in a shallower paleochannel to the west, yielded a shorter (~3,000 year) but higher resolution record. Mg/Ca ratios of Globigerinoides ruber and Globigerinoides sacculifer, in combination with the stable oxygen isotopic composition of G. ruber, allow for the estimation of sea surface temperature (SST), the stable oxygen isotopic composition of seawater ([delta]¹⁸O[subscript]sw), and salinity. Furthermore, the stable carbon isotopic composition of G. ruber illuminates trends in nutrient input and continental runoff. Based on decreased salinity estimates, a high sedimentation rate (~0.064 cm/yr), and low stable carbon isotopic values, core D45 records an interval of increased rainfall and continental runoff from 6-4 ka, in keeping with nearby speleothem and continental pollen records. Additionally, this core records coeval reduced SST values, a trend not recognized in regional deep-sea records, suggesting a strong terrestrial runoff effect on the sedimentary record. The Medieval Climate Anomaly and Little Ice Age are also tentatively recognized in SST data. Core D42 shows similar trends in data for the late Holocene, confirming that flooded fluvial paleovalleys can provide Holocene paleoclimatic records on continental shelves characterized by generally low sediment accumulation rates.
Keywords: Paleoclimate science; Geology; East Asian monsoons; Foraminifera; Geochemistry; Paleoclimate; Paleoclimatology--Holocene; Climatic changes--South China Sea; South China Sea